Chapter 15: LOOKING BACK. - Bricker, Victoria R. (Transactions of the American Philosophical Society, 2017)
In this article, the author focuses on his life's journeys. He mentions his transformational journeys to China, and states about his interest in language while mentioning his early experiences in Shanghai. He also mentions his exposer to multiple kinds of English such as German-speaking father and his sister and British dialect of his mother.